PENGGUNANAAN COMPRESSION STOCKING TERHADAP PENCEGAHAN DEEP VENOUS THROMBOSIS (DVT): LITERATUR REVIEW - Najihah, Najihah (Journal of Islamic Nursing, 2018)
Deep Venous Thrombosis (DVT) is a condition in which a clot forms in deep vein due to inflammation/ venous wall trauma or due to partial venous obstruction. Most DVT comes from lower extremities. Pulmonary embolism is a significant risk for DVT because the release of thrombus then follows the blood flow and is trapped in the pulmonary artery. Compression stocking is one of the compression therapies that helps prevent blood clots that form in the foot by applying pressure varies on each part of the foot. The purpose of this review literature is to determine the effectiveness of using the Compression stocking for prevention of DVT. The process of searching journal articles uses Google Scholar and several databases, namely Cocrane, Proques and Pubmed. Keywords included are "compression therapy", "compression stocking" and "deep venous thrombosis". Search results in each database based on keywords by reading the research abstract obtained 7 journal articles. The use of Compression stocking for prevention of DVT has been proven by several studies. This is because compression stocking works by exerting a compression level on the ankle with a gradual compression level. A pressure gradient or compression will ensure that blood flows towards the heart instead of reflux to the foot. But in the use of Compression stocking in the prevention of DVT, patients need to obtain information specifically about how to use it to avoid complications that might arise due to the use of Compression stocking.